The Axiological Challenges of Funding Islamic Education in Balancing Traditional Sincerity and Modern Financial Professionalism Trends - Abdul Rohman; Wafi Bahrul Ilmi; M. Muntohir (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study aims to analyze the axiological challenges in Islamic education funding, particularly regarding efforts to balance traditional values of sincerity with the demands of modern financial professionalism. Amid globalization, Islamic educational institutions face controversy between maintaining service ethics based on divine values and adopting formal financial management trends that prioritize accountability and efficiency. The research method used is descriptive qualitative with a literature study approach and philosophical analysis. The researcher examines the literature on educational financial management and philosophy of science journals to find a synthesis between the two paradigms that are often considered contradictory.The research results show that the main challenge lies in the potential desacralization of the value of sincerity when confronted with commercial standardization; however, financial professionalism has proven to be an urgent necessity to ensure the institution's sustainability transparently. The proposed solution is the reconstruction of funding axiology through the 'Spirituality-Based Professionalism' model, where modern accountability is not seen as a technical burden but as a form of trust that strengthens the value of sincerity itself. This research contributes a new theoretical framework for Islamic education management in formulating financial policies that preserve the dignity of pesantren or madrasah while remaining competitive with global governance standards. The findings are expected to serve as a strategic reference in mitigating financial integrity crises in Islamic educational institutions in the era of digital transformation.